Elucidating the Mechanism of the Oxygen Reduction Reaction for Pyrolyzed Fe-N-C Catalysts in Basic Media - Zagal-Moya, J; Zagal-Moya, J; Candia-Onfray, C; Candia-Onfray, C (Elsevier Inc., 2019)
The study of non-precious metal catalysts (NPMCs) as alternatives to platinum for oxygen reduction is crucial if the use of fuel cells is to become more widespread. Among NPMCs, pyrolyzed catalysts (Fe-N-C) are particularly promising in both basic and acid media. The characterization of active sites and the understanding of the oxygen reduction reaction (ORR) mechanism are crucial for the design of active Fe-N-C catalysts. In this study, we have tested the involvement of the metal centre in the ORR process at pH 13 for two pyrolyzed iron porphyrins. The pyrolyzed catalysts present a FeN4 active site structure similar to that of the porphyrin precursors. Regarding the mechanism, we have found evidence for the crucial role of the Fe(II) centres. There is a direct relation between the Fe(III)/(II) redox transition of the catalysts and the onset potential of the ORR, showing that the electrogeneration of Fe(II) from Fe(III)OH – controls the catalysis. The poisoning of iron centres with CN − induces a decrease in the ORR activity. However, the onset potential for H 2 O 2 generation remains unchanged. The Tafel plots show two different slopes at high and low overpotentials. Based on these results, we propose two different mechanisms, both dependent on the redox potential of the catalysts and the Fe–O 2 binding energy. © 2019 The Authors